Development of internship hiring mobile application for BeMyIntern Malaysia / Muhammad Izzham Shahinazlee - Shahinazlee, Muhammad Izzham (2017)
BeMyIntern Malaysia is a service provider, bridging internship applicants with employers’ internship job postings. The current system is found to be lacking in terms of catering to users that are searching for internship positions while on the move. By proposing a mobile application, problems such as the lack of mobility in using the current system, absence of immediate notification, and limited coverage of service can be minimized. The methodology chosen to carry out this project is via the traditional Software Development Life Cycle (SDLC) using Waterfall model. This model consists of phases such as requirements gathering and analysis, design, implementation, testing, and maintenance. However, the phases adopted for this project just covers until implementation as the later stages are deemed unnecessary. Findings and results of this project includes the achievement of each objective, by developing an System Requirements Specification (SRS) for the requirements phase, creating an System Design Document (SDD) for the design phase, and finalizing the mobile application for the implementation phase. Each of these objectives are documented to provide transparency and as reference for future revision. In the requirement gathering and analysis phase, six (6) use cases are identified – manage account, manage resume, view resume, view jobs, manage jobs, and check job application. All the said use cases are then used as a base to design the mobile application in the design phase through storyboards, and Design Class Diagram. In the implementation phase, the design is realized with coding the Android mobile application using Java. Lastly, future work of this project would mean the enhancement of mobile technologies by applying newer frameworks and methods.